Compression moulding of composites with hybrid fibre architectures - Corbridge, D.M.; Harper, Lee Thomas; De Focatiis, Davide S.A.; Warrior, N.A. (Elsevier, 2017)
Advanced Sheet Moulding Compounds (ASMC) and unidirectional (UD) prepregs have been co-compression moulded to form a hybrid composite material. In-mould flow influences the UD fibre architecture in two ways. When UD fibres are aligned transversely to the ASMC flow direction, shearing occurs which causes local changes in fibre volume fraction and fibre waviness. When the UD fibres are aligned with the ASMC flow direction, ply migration takes place. In general, the composite stiffness follows a rule of mixtures relationship, with the stiffness proportional to the UD fibre content.